Seed production of spice species: current situation and perspectives (Research, Society and Development, 2021)
Spices are of global importance due to their most diverse forms of usability, whether as food, aromatic or medicinal. Furthermore, they move relevant amounts in the economic market and the production of spice seeds is an activity that has the capacity to boost the development of an entire region, and still has a strong economic and social appeal, generating employment and income in agriculture thanks to the high demand for labor. This review will deal with the seed production of the following spice plants: onion, coriander, parsley, black pepper and aim to define the scenario, production and future prospects for the production of the evaluations. Depending on the current situation of the species mentioned above, it is observed that, despite the wide range of spice species, these are little explored in Brazil, a factor that is written by the law of supply and demand. But the perspectives are that their production is becoming more and more representative in the market, due to the growing demand for these species.